∫ 0 1 x 2 0 1 6 ( 1 − x ) 2 0 1 7 d x
If the above integral can be expressed in the form b a , where a and b are coprime positive integers, find a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The function x 2 0 1 6 ( 1 − x ) 2 0 1 7 can be integrated by parts to remove the x term like such:
∫ 0 1 x 2 0 1 6 ( 1 − x ) 2 0 1 7 = 2 0 1 8 − x 2 0 1 6 ( 1 − x ) 2 0 1 8 − 2 0 1 8 ∗ 2 0 1 9 2 0 1 6 x 2 0 1 5 ( 1 − x ) 2 0 1 9 − . . .
− 2 0 1 7 ! 4 0 3 3 ! 2 0 1 6 ! ( 1 − x ) 4 0 3 3
The only term we care about is the last term since when plugging in the limits into x , it is the only term that does not go to zero.
Plugging the limits in results in ∫ 0 1 x 2 0 1 6 ( 1 − x ) 2 0 1 7 = 4 0 3 3 ! 2 0 1 6 ! ∗ 2 0 1 7 ! = ( 2 0 1 6 4 0 3 3 ) 1 a binomial coefficient, as pointed out to me by @Kyle Coughlin .
The binomial coefficient returns an integer, b , and so a = 1
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 1 x 2 0 1 6 ( 1 − x ) 2 0 1 7 d x = B ( 2 0 1 7 , 2 0 1 8 ) B ( m , n ) is beta function. = Γ ( 4 0 3 5 ) Γ ( 2 0 1 7 ) Γ ( 2 0 1 8 ) Γ ( x ) is gamma function. = 4 0 3 4 ! 2 0 1 6 ! 2 0 1 7 ! = 2 0 1 7 ! 2 0 1 7 ! 2 0 1 7 ⋅ 4 0 3 4 ! 1 = 2 0 1 7 ( 2 0 1 7 4 0 3 4 ) 1 = b a
Both a and b are integers and a = 1 .
References